Interpolation Functions of q-Extensions of Apostol's Type Euler Polynomials. (23rd August 2009) - Hwang, Kyung-Won; Kim, Young-Hee; Kim, Taekyun
Abstract : The main purpose of this paper is to present newq -extensions of Apostol's type Euler polynomials using the fermionicp -adic integral onℤ p . We define theq -λ -Euler polynomials and obtain the interpolation functions and the Hurwitz type zeta functions of these polynomials. We defineq -extensions of Apostol type's Euler polynomials of higher order using the multivariate fermionicp -adic integral onℤ p . We have the interpolation functions of theseq -λ -Euler polynomials. We also give( h, q ) -extensions of Apostol's type Euler polynomials of higher order and have the multiple Hurwitz type zeta functions of these( h, q ) -λ -Euler polynomials.